PENGARUH KEJELASAN SASARAN ANGGARAN TERHADAP KEEFEKTIFAN PENGENDALIAN (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2014)
In economic globalization these days, company in Karesidenan Surakarta tends to orient at market compartment. None again maximal advantage pursuer. Searching maximum advantage will result the bonanza in short-range, but bringing instability on a long term. In company activity, budget requirement will earn in telling to represent the really matter require to get the attention, because capital stream represent the primary factor of impeller and activator in its effort to grab the market compartment, utilize to maximize the rights of stockholder through the action financial, especially fund allocation. Bibliography stuoy of performed within this research frame lay open that budget applying can improve the operation function in company management. Hence writer makes the research hypothesis of following: